Evaluation of oral pharmacokinetics, in vitro metabolism, blood partitioning and plasma protein binding of novel antidiabetic agent, S009‐0629 in rats. Issue 4 (10th July 2018) - Valicherla, Guru Raghavendra; Italiya, Kishan Shamjibhai; Gupta, Chandra Prakash; Mishra, Shachi; Riyazuddin, Mohammed; Syed, Anees Ahmed; Singh, Sandeep Kumar; Shahi, Sudhir; Taneja, Gaurav; Wahajuddin, Mohammad; Goel, Atul; Gayen, Jiaur Rahaman
Abstract: S009‐0629 [methyl‐8‐(methylthio)‐2‐phenyl‐6‐p‐tolyl‐4, 5‐dihydro‐2H‐benzo[e]indazole‐9‐carboxylate] is a novel antidiabetic agent with PTP1B inhibitory activity. In this study, we have investigated the in vitro metabolic stability, plasma protein binding, blood partitioning, and oral pharmacokinetic study of S009‐0629 in rats. The plasma protein binding, blood partitioning, and metabolic stability were determined by HPLC method. The oral pharmacokinetic study was analyzed by liquid chromatography coupled mass spectrometry (LC‐MS/MS) method. The plasma protein binding of S009‐0629 using modified charcoal adsorption method at 5 and 10 µg/mL was 80.58 ± 1.04% and 81.95 ± 1.15%, respectively. The KRBC/PL of S009‐0629 was independent of concentration and time. The in‐vitro half‐life of S009‐0629 at 5 and 10 µM using rat liver microsomes was determined as 273 ± 24.46 and 281.67 ± 26.53 min, respectively. After oral administration, S009‐0629 exhibited C max 55.51 ± 1.18 ng/mL was observed at 18 hr ( t max ). S009‐0629 was found to have the large apparent volume of distribution (1, 894.93 ± 363.67 L/kg). Oral in‐vivo t 1/2 of S009‐0629 was found to be 41.23 ± 5.96 hr. A rapid and highly sensitive LC‐MS/MS method was validated for S009‐0629 in rat plasma. S009‐0629 has high plasma protein binding and low hepatic extraction. S009‐0629 has no affinity with human P‐gp and BCRP in ATPase assay. After oral dosing, S009‐0629 has slow absorption and elimination in rats.